Modelación y simulación del proceso de fundición para el zinc y aluminio. - Escobar Ruiz, Miguel Alejandro (2021)
The purpose of this research project was to develop the modeling and simulation of the zinc and aluminum smelting processes; very important processes from the perspective of the students of the Cotopaxi Higher Technological Institute in their laboratory practices, to the operation of the metallurgical industries of the city of Latacunga. Among the specific tasks, the work identified and mathematically modeled the thermal behavior of the zinc and aluminum smelting process; Also, he categorized the zinc and aluminum smelting processes that govern the mathematical and computational dimensioning. In addition, the zinc and aluminum smelting processes were established in MATLAB and the smelting process was evaluated in a GUIDE interface of the aforementioned program. The methodology used was of the Extreme Programming (XP) type and was characterized by five main dimensions: the compilation of the characteristics of the melting furnace, the identification of the variables in a linear system, the mathematical modeling (pre-processed, processed and post-processed), the simulation of the mathematical model in MATLAB GUIDE and verification of results; each process had its algorithm, iteration and debugging. Among the results obtained from the foundry furnace simulator are that aluminum melts at an average temperature of 601.86 ºC in an average time of 22.55 minutes, while zinc melts at a temperature of 387 ºC in an average time of 27.14 minutes. With the experimental data it was possible verify the proper functioning of the simulation, the differences found in the preheating process is 10.5% for aluminum and 9.6% for zinc, while in the casting process it is 9.7% for the aluminum and 8.9% for zinc in most cases, showing that the model has great potential to simulate the test oven.